A rehabilitative approach beyond the acute stroke event: a scoping review about functional recovery perspectives in the chronic hemiplegic patient - Paolucci, Teresa; Agostini, Francesco; Mussomeli, Elena; Cazzolla, Sara; Conti, Marco; Sarno, Francescapia; Bernetti, Andrea; Paoloni, Marco; Mangone, Massimiliano (Frontiers in Neurology, 2023)
Background Stroke is a main cause of disability worldwide and its neuro-rehabilitative management is not limited to the acute phase but requires continuity in the rehabilitation approach especially in the chronic phase. The aim of this scoping review was to highlight the different treatment opportunities available in neurorehabilitation, effective for patients with chronic stroke sequelae, not only in terms of maintaining motor function but also improving it. Methods The literature search was conducted using the following databases: MEDLINE (PubMed), PEDro, Scopus, Web of Science (WOS), Cochrane from 2012 to February 2023. We selected Randomized Clinical Trials in English dealing with neurorehabilitation strategies in chronic hemiplegic patients after stroke focusing on motor function, muscular strength, gait, postural balance, spasticity, and quality of life. Results According to the inclusion criteria, 47 articles were selected for our review. All of them were analyzed following the primary outcome and the rehabilitation technique used. Despite the different protocols used within the same technique and despite the chronicity of the disease, all studies report an improvement after the rehabilitation treatment of motor function and quality of life. Conclusion The literature analyzed invites us to reflect respect to neurorehabilitation approach to the patient with chronic stroke sequelae often considered to have as its objective the maintenance of the present motor function and contain disability: instead, the review reports how, even in chronicity, the patient always reports margins of statistically and clinically significant improvement. The chronic stroke rehabilitation over 6 months has been proved effective in obtaining recovery in different settings.